2021
DOI: 10.1049/cvi2.12036
|View full text |Cite
|
Sign up to set email alerts
|

Control the number of skip‐connects to improve robustness of the NAS algorithm

Abstract: Recently, the gradient-based neural architecture search has made remarkable progress with the characteristics of high efficiency and fast convergence. However, two common problems in the gradient-based NAS algorithms are found. First, with the increase in the raining time, the NAS algorithm tends to skip-connect operation, leading to performance degradation and instability results. Second, another problem is no reasonable allocation of computing resources on valuable candidate network models. The above two poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Similarly, in the case of the VGG-16 backbone: the degradation of performance when masking inputs using the ViT-specific procedure is clear, although less pronounced than what it was for ResNet-50. This can be attributed to the fact that the VGG-16 architecture has no skip connections: in [59] it has been shown that limiting the number of skip connections improves robustness. Summarily, this ablation experiment demonstrates the importance of handling the perturbation of inputs in the case of CNN and ViT backbones differently, in agreement with what we proposed in Section III-C3.…”
Section: ) Mismatched Backbone-masking Procedures Combinationmentioning
confidence: 99%
“…Similarly, in the case of the VGG-16 backbone: the degradation of performance when masking inputs using the ViT-specific procedure is clear, although less pronounced than what it was for ResNet-50. This can be attributed to the fact that the VGG-16 architecture has no skip connections: in [59] it has been shown that limiting the number of skip connections improves robustness. Summarily, this ablation experiment demonstrates the importance of handling the perturbation of inputs in the case of CNN and ViT backbones differently, in agreement with what we proposed in Section III-C3.…”
Section: ) Mismatched Backbone-masking Procedures Combinationmentioning
confidence: 99%